2019
DOI: 10.1007/s00464-019-06738-6
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden of appendectomy for appendicitis: a population-based cohort study

Abstract: Background Few large-scale epidemiologic studies evaluate the clinical and economic burden of appendicitis. These data may impact future research and treatment strategies. In this study, the objective was to determine the burden of appendectomy for appendicitis in terms of incidence rates, length of hospital stay (LOS) and hospital costs on a national level. In addition, outcomes were compared for subgroups based on surgical treatment, age and hospital setting. Methods Observational retrospective population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
0
16
1
Order By: Relevance
“…For example, the global financial crisis and changes in the registration of electronic health records in the Netherlands around 2012 might have led to a reduction in number of procedures. However, the significant decrease in 2012 was not observed for other surgical procedures 19‐21 . Thereby, it remains unclear why such a pivotal decrease in number of adenotonsillectomies was observed in 2012.…”
Section: Discussionmentioning
confidence: 93%
“…For example, the global financial crisis and changes in the registration of electronic health records in the Netherlands around 2012 might have led to a reduction in number of procedures. However, the significant decrease in 2012 was not observed for other surgical procedures 19‐21 . Thereby, it remains unclear why such a pivotal decrease in number of adenotonsillectomies was observed in 2012.…”
Section: Discussionmentioning
confidence: 93%
“…However, two trainees continued to have high complications rates throughout the training period. Complication rates for appendectomy are low (about 5%) (15,16). From the local appendectomy register the complication rate was 6.6% for laparoscopic appendectomy and 10.5% for open appendectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, no firm conclusion can be drawn concerning the frequency of non-operative treatment. However, De Wijkerslooth et al demonstrated a yearly decrease in the incidence of acute appendicitis [ 31 ]. Given the similar number of performed appendectomies in 2020 compared to 2019 in our study, it is less likely that a conservative treatment of acute appendicitis was implemented on a wider scale.…”
Section: Discussionmentioning
confidence: 99%